Rebel Women : Staging Ancient Greek Drama Today. - Wilmer, Stephen (Plays and Playwrights., 2014)
A collection of essays by many distinguished contributors, focused on the portrayal of rebel women in ancient Greek drama. Ancient Greek drama provides the modern stage with a host of powerful female characters who stand in opposition to the patriarchal structures that seek to limit and define them. For contemporary theatre directors their representation serves as a vehicle for examining and illuminating issues of gender, power, family and morality, as germane today as when the plays were first written. Rebel Women brings together essays by leading writers from across different disciplines exa.